2007
DOI: 10.1177/0894439307305625
|View full text |Cite
|
Sign up to set email alerts
|

Trickle-Down Technology? The Use of Computing and Network Technology in State Legislative Campaigns

Abstract: Does a lag effect exist in the integration of technology into state legislative campaigns? Have state legislative campaigns followed the example of congressional campaigns and become users of voter files, web sites, and other forms of electronic voter communication? Using a survey of state legislative candidates in two states from the 2006 election cycle, the author probes candidates on their use of 18 technological elements. Legislative professionalism, party affiliation, professionalism of a campaign, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 2 publications
0
14
0
1
Order By: Relevance
“…First, although not all state legislative candidates use websites, it is likely that most do, and in the states examined here the vast majority did. Although Herrnson, Stokes-Brown, and Hindman (2007) found that only about 40% of state legislative candidates used websites, Rackaway (2007) found about two-thirds of candidates in Kansas and North Carolina had websites. It is also likely that since 2007 the use of websites by state legislative candidates has increased as the use of the Internet generally increased in that time period.…”
Section: Methodsmentioning
confidence: 99%
“…First, although not all state legislative candidates use websites, it is likely that most do, and in the states examined here the vast majority did. Although Herrnson, Stokes-Brown, and Hindman (2007) found that only about 40% of state legislative candidates used websites, Rackaway (2007) found about two-thirds of candidates in Kansas and North Carolina had websites. It is also likely that since 2007 the use of websites by state legislative candidates has increased as the use of the Internet generally increased in that time period.…”
Section: Methodsmentioning
confidence: 99%
“…With similar practices seeming to occur in other states with high political action in 2010 (Kaye, 2010), the tools created within Illinois are likely to be part of the media landscape for election cycles to come. Although the campaigns producing these sites in 2010 were from more advanced and highly publicized races (campaigns within the sample are gubernatorial, senatorial, and select congressional races, with one exception: a hotly contested countywide race that included Chicago), these practices are likely to occur on a more widespread level because campaigns' use of new media can be characterized by a trickledown effect, with tactics moving from the presidential level to popular federal and gubernatorial races, followed slowly by state-level races (Rackaway, 2007). Because one measure of success is the ability to gain earned media attention, news and blog coverage, such as Kaye's (2010) piece that describes many "hit sites" that bear similarities to those of the Illinois-based sample, increases the probability that these sites will be mimicked.…”
Section: Methodsmentioning
confidence: 99%
“…In all of those instances, the importance of studying mobilization in the context of online political communication lies in the fact that, through mobilization, this type of communication can successfully lead to measurable effects in offline behavior. For example, Rackaway (2007) found that the use of online fund-raising 9 practices had a positive effect on votes. Online mobilization features make it easier for citizens to participate in online political activities.…”
Section: Mobilizationmentioning
confidence: 99%